Serum th1 and th2 cytokines in systemic lupus erythematosus patients : its relationship with disease activity and organ involvement - Kanowah, Eshan (2006)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease that may result from defective functions of the immunoregulatory T cell circuits. Cytokines play an essential role in molding the quality of an immune response to foreign or self-antigens. With the growing literature regarding cytokine production in autoimmune diseases, an important role for an active Th 1 response, characterized by production of IFN-y, IL-2, fL- 12 and TNF-a has become evident. On the contrary, there have also been repeated observations of high levels of type 2 cytokines (IL-4, IL-5, IL-l 0, IL-6 and IL-13) particularly in the systemic autoimmune diseases. Objectives: To determine the circulating serum levels of two Th I (IL-2, IFN-y) and two Th2 (IL-6, IL-13) cytokines in patients with systemic lupus erythematosus (SLE), to compare serum level of IL-2, IFN- y, IL-6 and IL-13 with the disease activity in SLE patients and to assess the relationship between serum level of cytokines (IL-2, IL-6, lL- 13 and IFN-y) and different organ involvement in SLE patients. Methodology: We included 90 SLE patients and 30 healthy controls in this comparative cross sectional study carried out in Hospital Universiti Sains Malaysia (USM) and General Hospital Kota Bharu from October 2003 until September 2005 by selecting SLE patients in medical wards and outpatient clinics. Serum levels of cytokines were measured by ELISA (IL-2, interferon (IFN) y, IL-6 and IL-13) as well as antidsDNA, ANA, C3 and C4 complement levels were determined. Disease activity was recorded according to the Systemic Lupus Erythematosus Disease Activity Index(SLEDAI) and classified as high activity (SLEDAI > 8) or low activity (SLEDAI :S 8). Different organ affected at any time during the course of the disease was recorded. Results: The mean age of the patients was 31 .0± 10.8 years. Out of 90 SLE patients, 81 were females (90%) and 9 males (10%). Majority was Malay (92.2%) and the rest was Chinese (7.8%). 52 patients (57.8%) were inactive SLE (SLEDAI score 0-8) and 38 patients (42.2%) active SLE (SLEDAI score >8). Serum levels of cytokines in SLE patients were significantly higher than in healthy control with the exception of IL-2 (IFN' Y p<O.OO 1, IL-6 p<O.OO 1, IL-13 p=0.002, IL-2 p= 0.639). There were also significant differences between active and inactive SLE patients with the exception of IL-2 (IL-6 p <0.001 , IL-1 3 p = 0.009, IFN-y p <0.001and IL-2 p =0.087). There was a positive correlation between Th I (IFN- y) and Th2 (IL-6 and IL-1 3) cytokines with the disease activity ((IFN-y p=0.002, IL-6 p<O.OO 1, IL-1 3 p=0.006, IL-2 p= 0.151 ). There was significant correlation between serum level of IL-1 3 and musculoskeletal involvement (p =0.0 16) and also IL-6 with haematological involvement (p =0.003). Conclusion: The serum levels of Th2 (IL-6 and IL-1 3) and Th I (IFN- y) cytokines were significantly elevated and correlated with disease activity in SLE patients. Serum cytokine level could provide useful information about disease activity in SLE patients.